NCMP-07. TREATMENT-INDUCED CEREBRAL NECROSIS IN GLIOMAS: THE OHIO STATE UNIVERSITY COMPREHENSIVE CANCER CENTER (OSUCCC) EXPERIENCE. (9th November 2020) - Rayi, Appaji; Alnahhas, Iyad; Palmer, Joshua; Raval, Raju; Slone, Wayne; Ong, Shirley; Giglio, Pierre; Puduvalli, Vinay
Abstract: INTRODUCTION: Treatment-induced cerebral necrosis (TN) is a challenging complication encountered in neuro-oncology. Diagnosis and treatment of TN remains poorly defined. METHODS: In this single institution, retrospective study, consecutive patients with gliomas and TN between 01/01/2012 and 04/20/2020 at the OSUCCC were identified. Details of the tumor treatment, molecular markers, radiological and pathological findings of TN, as well as treatment, recurrence rate and management upon recurrence were collected. RESULTS: Of the 53 patients analyzed, 37 had glioblastoma, 7 had anaplastic oligodendroglioma and 9 had grade II or III astrocytoma. MGMT promoter hypermethylation was present in 31/50 (59%) and IDH mutation in 17/53 (32%). Diagnosis of TN was based on histology in 43/53 (81%) or clinical/radiographic features in 10/53 (19%). Worsening of focal weakness (36%), seizures (9%) or being (30%) were common presentations at TN diagnosis. Patient with right compared to left hemisphere involvement were more symptomatic at TN diagnosis. (p=0.049). Bevacizumab (BEV) (51%), resection (28%), steroids only (9%) or Laser Interstitial Thermal Therapy (6%) were used to treat TN. Steroids were weaned off in 20/27 (74%) after receiving BEV. Among all treatments, BEV was significantly associated with a better outcome (resolution or partial improvement of enhancement in 84.6%) (p=0.0006, Bonferroni corrected p< 0.005). TN Recurrence occurred in 36%, 70% and 100% of the patients treated with BEV, resection and LITT respectively. The median duration to TN recurrence was 10 weeks (range: 3–70 weeks). Initial treatment used for TN, MGMT methylation and IDH mutation status did not predict TN recurrence. (p=0.074; p=0.819; p=0.607 respectively). CONCLUSIONS: BEV appears to be a superior treatment to control TN overall. Recurrence of TN in patients previously treated with BEV was 36%. There was no difference in the risk of developing recurrent TN based on MGMT or IDH status.